From these roots : my fight with Harvard to reclaim my legacy - Lanier, Tamara, 1962-; Welch, Liz, 1969- (Crown, 2025)
"Tamara Lanier grew up listening to her mother's stories about her ancestors. As Black Americans descended from enslaved people brought to America, they knew all too well how fragile the tapestry of a lineage could be. As her mother's health declined, she pushed her daughter to dig into those stories. "Tell them about Papa Renty," she would say. It was her mother's last wish. Thus begins one woman's remarkable commitment to document that story. Her discovery of an eighteenth-century daguerreotype, one of the first-ever photos of enslaved people from Africa, reveals a dark-skinned man with short-cropped silver hair and chiseled cheekbones. The information read "Renty, Congo." All at once, Lanier knew she was staring at the ancestor her mother told her so much about-Papa Renty. In a compelling story covering more than a decade of her own research, Lanier takes us on her quest to prove her genealogical bloodline to Papa Renty's that pits her in a legal battle against one of the most powerful institutions in the country, Harvard University. The question is, who has claim to the stories, artifacts, and remnants of America's stained history-the institutions who acquired and housed them for generations, or the descendants who have survived? From These Roots is not only a historical record of one woman's lineage but a call to justice that fights for all those demanding to reclaim, honor, and lay to rest the remains of mishandled lives and memories"--